Challenges of urban education and efficacy of school reform - Hunter, Richard C., Dr.; Brown, Frank, 1935- (Amsterdam ; London : JAI, 2002)
Urban education is the primary target of the school reform movement and remains the most difficult to assess and repair. The crisis in urban school systems mirrors many of the problems found in big cities - poor economic conditions for schools and families, personnel shortages and high turnover rates, improper facilities and materials, and political struggles over issues of structure and control. This book analyses the problems affecting urban schools and their students and the efforts that have been made to make these schools more accountable and effective. This book is organized in three parts. Part one provides an overview of many of the issues facing urban school districts, their students and their communities including meeting the needs of racially, ethnically, linguistically and culturally diverse populations, financing schools located in economically disadvantaged areas, and attracting and maintaining qualified teachers and administrators. Part two examines the impact demands for increased accountability and equity influence urban education reform. The issues discussed in this section include academic standards and high stakes testing, technology and the digital divide, the role of leadership and impact of teacher shortages, and school finance and public policy. Part three focuses on strategies developed to reform and improve urban school systems. These chapters examine federal education policy, the impact of school choice and related issues such as privatization and vouchers, the influence of community involvement, and state sponsored reform and reorganization efforts.
Introduction: challenges of urban education efficacy of urban education / Richard C. Hunter, Frank Brown -- Diversity and reform / A. Reynaldo Contreras -- Historical struggles for equity: Politics of education and language policies and its implications for Asian Americans / Ji-Yeon O. Jo, Xue Lan Rong -- Reconstitution, small schools, school-based management, etc. / James E. Lyons -- Update on school desegregation / Charles J. Russo -- Back to the future with the end of Brown / Frank Brown -- Discrimination in tracking and specialized education programs / Richard C. Hunter, Saran Donahoo -- Urban economics and financial factors affecting education / Stephen B. Lawton -- The structure of inequality: tracking and educational opportunity in America's public schools / Paul Green -- The digital divide in America's public schools / Philip T.K. Daniel -- Supervision's primary task: synthesizing professional development to meet individual teacher needs and attain school organizational goals / Stephen Earl Lucas -- School leadership for 21st-century urban communities / Leonard A. Valverde -- Adequacy issues in financing urban schools / James G. Ward -- Standardized testing and assessment policy: impact on racial minorities and implications for educational leadership / Dawn G. Williams, Laurence Parker -- Instructional efficiency versus social reform: fundamentals of the tracking debate / Arthur E. Lehr -- Initiating work teams to reform the american high school / Terri H. Mozingo -- Choice, vouchers and privatization as education reform or the fulfillment of Richard Nixon's southern strategy? / Frank Brown -- Filing for academic bankruptcy: the impact and economics of state takeovers / Richard C. Hunter, Saran Donahoo -- African American parental involvement in urban school reform: implications for leadership / Linda C. Tillman.
Description based on print version record.
Keywords: Education, Urban -- United States; Educational change -- United States; Organization & management of education; Urban communities; Education -- Educational Policy & Reform -- General